Water recovery rate and isotopic signature of cryogenic vacuum extracted spiked soil water following oven‐drying at different temperatures. Issue 6 (8th June 2021) - Wen, Mingyi; Si, Bingcheng; Lu, Yanwei; Wang, Hongxiu
Abstract: Extracting water from soils is often a critical step for obtaining soil water isotope information. Cryogenic vacuum extraction (CVE), the most widely used laboratory‐based removal technique, produces biased isotope composition and the mechanisms causing the biases remain uncertain. Here, we conducted spiking tests on soil samples oven‐dried at 105 and 205°C, respectively. The recovery rate and isotopic composition of the extracted water were analysed. Our results show that conventional oven‐drying (105°C) was not sufficient to liberate tightly bound water from soils but oven‐drying at temperatures above 205°C was. Part of the tightly bound water in soil was extracted by CVE, because the extraction capacity of CVE (heating at 95°C) was equivalent to oven‐drying at temperature between 105 and 205°C. Moreover, the two pretreatments yielded markedly differences in water recovery rates. And with increasing ratios of clay contents to water contents, the recovery rates of the pretreated soil at 105°C trended upward above 100%, but that of 205°C trended downward below 100%. Further, the 2 H and 18 O signatures of the extracted water from the soil pretreated at 205°C were both depleted relative to reference water, but the pretreatment at 105°C showed enriched 18 O and depleted 2 H. This suggests that oxygen isotope exchange may have occurred between tightly bound water and soil minerals, resulting in enriched 18 O in water for the 105°C pretreatments. For the 205°C pretreatment, pre‐existing soil water was completely removed and relative to spiking water, isotopic signatures of the extracted water followed equilibrium fractionation law due to incomplete extraction. Therefore, our results suggested that the biased isotopic signatures of water extracted by CVE may be partially due to incomplete extraction and mixture of added water with the residual tightly bound water that pre‐exists before spiking. Abstract : The critical oven‐dry temperature that can remove soil bulk water was determined. Pretreatment oven‐drying temperature significantly impacts the obtained recovery rate and isotopic composition for a spiking test. Incomplete extraction and pre‐existing tightly bound water before spiking bias cryogenic vacuum extraction.